Electrochemical properties of La0.5Sr0.5Fe0.95Mo0.05O3−δ as cathode materials for IT-SOEC. Issue 51 (28th September 2021) - Hou, Yunting; Wang, Yadun; Wang, Lijun; Zhang, Qifei; Chou, Kuo-chih
Abstract : Mo doping solves the SrCO3 generation of LSF as SOEC cathode and increases the oxygen deficiencies of the material, which make LSFMo possess higher electrolytic performance. Abstract : Solid oxide electrolysis cells (SOECs) are a new type of high-efficiency energy conversion device that can electrolyze CO2 efficiently and convert electricity into chemical energy. However, the lack of efficient and stable cathodes hinders the practical application of CO2 electrolysis in SOECs. Herein, a novel perovskite oxide La0.5 Sr0.5 Fe0.95 Mo0.05 O3− δ (LSFMo) is synthesized and used as a cathode for SOECs. The introduction of Mo significantly improves the CO2 tolerance of the material in a reducing atmosphere and solves the problem of SrCO3 generation in the La0.5 Sr0.5 FeO3− δ material. Mo ion doping promotes the conductivity in a reducing atmosphere and increases the oxygen deficiencies of the material, which lowers the ohmic resistance ( R s ) of the material and significantly improves the CO2 adsorption and dissociation in the middle-frequency of polarization resistance ( R p ). For example, R p decreases from 0.49 to 0.24 Ω cm 2 at 800 °C under 1.2 V. Further, the reduction of R s and R p increases the performance improvement, and the current density is increased from 1.56 to 2.13 A cm −2 at 800 °C under 2 V. Furthermore, LSFMo shows reasonable short-term stability during the 60 h stability test.